Personality Traits and Stress Coping Mechanisms Among Nursing Students During Thesis Preparation - Ning Ayu Hotijah; Vivin Nur Hafifah; Arif Eko Trilianto (Genius Publishing (CV. Gerbang Ilmu Nusantara), 2025)
Introduction: Thesis preparation is a mandatory academic requirement that often becomes a significant source of stress among students. Individual differences in personality traits may influence how students cope with academic stress. Effective stress coping strategies are essential to help students manage psychological pressure during thesis completion.Objectives: This study aimed to analyze the relationship between personality traits and stress coping mechanisms among nursing students during thesis preparation.Methods: This study employed a quantitative correlational design with a cross-sectional approach. A total of 152 respondents were selected using a purposive sampling technique. Data were collected using structured questionnaires measuring personality traits and stress coping mechanisms. Statistical analysis was performed using the Spearman’s rho correlation test with a significance level of p < 0.05.Results: The findings indicated that the majority of students exhibited extroverted personality traits and tended to use positive stress coping mechanisms. A statistically significant relationship was found between personality traits and stress coping (p < 0.05), suggesting that personality characteristics influence how students manage stress during thesis preparation.Conclusions: Personality traits are significantly associated with stress coping mechanisms among nursing students. Students with more adaptive personality characteristics tend to use more positive coping strategies, which may support successful thesis completion.